Assessment of the effect of an Interactive Dynamic Referral Interface (IDRI) on the quality of referral letters from general practitioners to gastroenterologists: a randomised cross-over vignette trial. Issue 6 (30th June 2017) - Eskeland, Sigrun Losada; Brunborg, Cathrine; Rueegg, Corina Silvia; Aabakken, Lars; Lange, Thomas de
Abstract : Objectives: We evaluated whether interactive, electronic, dynamic, diagnose-specific checklists improve the quality of referral letters in gastroenterology and assessed the general practitioners' (GPs') acceptance of the checklists. Design: Randomised cross-over vignette trial. Setting: Primary care in Norway. Participants: 25 GPs. Intervention: The GPs participated in the trial and were asked to refer eight clinical vignettes in an internet-based electronic health record simulator. A referral support, consisting of dynamic diagnose-specific checklists, was created for the generation of referral letters to gastroenterologists. The GPs were randomised to refer the eight vignettes with or without the checklists. After a minimum of 3 months, they repeated the referral process with the alternative method. Main outcome measures: Difference in quality of the referral letters between referrals with and without checklists, measured with an objective Thirty Point Score (TPS). Difference in variance in the quality of the referral letters and GPs' acceptance of the electronic dynamic user interface. Results: The mean TPS was 15.2 (95% CI 13.2 to 16.3) and 22.0 (95% CI 20.6 to 22.8) comparing referrals without and with checklist assistance (p<0.001), respectively. The coefficient of variance was 23.3% for the checklist group and 39.6% for the non-checklist group. Two-thirds (16/24) of the GPs thought they had included more relevant information in the referrals with checklists, and considered implementing this type of checklists in their clinical practices, if available. Conclusions: Dynamic, diagnose-specific checklists improved the quality of referral letters significantly and reduced the variance of the TPS, indicating a more uniform quality when checklists were used. The GPs were generally positive to the checklists.